At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
to solve this, first you need to jump back the clock. so 18 minus 12 is 6. scince at that time joseph was 4 times older, 6 times 4 is 24. add that to 12 and you get 36. but we need to check our work. if 36 minus 18 isint 18 then we screwed up. but, we didnt. so now, Kara is 18 years old and Joseph is 36 years old.
Let us call X Kara's age and Y Joseph's.
We know that
X=Y-18
Y-12=4(X-12)
We can deduce from the second that
Y-12=4X-48
Y=4X-36
So if you replace Y in the first equation you get:
X=(4X-36)-18
X=4X-54
3X=54
X=18
so we can deduce that 18=Y-18 which means that Y=36
Kara is 18
Joseph is 36
We know that
X=Y-18
Y-12=4(X-12)
We can deduce from the second that
Y-12=4X-48
Y=4X-36
So if you replace Y in the first equation you get:
X=(4X-36)-18
X=4X-54
3X=54
X=18
so we can deduce that 18=Y-18 which means that Y=36
Kara is 18
Joseph is 36
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.